LACK OF AWARENESS AMONG THE CANDIDATE FEMALES HINDERS CERVICAL CANCER SCREENING; A COHORT STUDY FROM PERADENIYA AND KANDY TEACHING HOSPITAL - Subhashini Muhandiram; Suranga Pradeep Kodithuwakku; Thusitha Kumara Karunarathna; Eranga Himalee Siriweera; Thilini Kumari Weerasinghe; Chathura Jayanath Ratnayake (Sri Lanka Journal of Medicine, 2019)
Background Cervical cancer (CC) is the second leading type of female cancer in Sri Lanka. Unawareness of risk factors, prevention methods and socio-economic-cultural factors hinder women in participating in current day screening programs. The study intended to assess factors related to uptake of women in to cervical cancer screening using a cohort of gynecology clinic attendees. Materials and Methods A descriptive cross sectional study was conducted on a purposively sampled 150 women attending outpatient gynecology clinics at the Teaching Hospitals in Kandy and Peradeniya. Knowledge, attitude and practices related to cervical cancer screening and prevention were assessed through a self-administered, structured and pre-tested questionnaire and statistically analyzed using the SPSS software. Results Among 150 women participated, only 48 % of the women have had the test previously at least once. Age of the women, parity, marital status, awareness of Pap test, overall knowledge and practices on cervical cancer screening and risk factors were significantly (p